Pengaruh Penggunaan Gadget bagi Keluarga di Paroki Santo Antonius Padua Taratara - Paulus Joseph Mentang; Fransiska Karamoy (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
Technological progress (Gadgets) aims to make all human activities easier, but this must also be accompanied by a wise attitude of humans as users of this technology. Gadgets function to facilitate virtual interaction and communication, but if used unwisely they have the potential to be bad for communication and interaction between users. This article carries the title "The Effect of Using Gadgets on Families in St. Mary's Parish. Anthony Padua Taratara”. The background to this article stems from several problems, namely how gadgets are used in families at St. Antonius Padua Taratara, how is family life in St. Patrick's Parish? Antonius Padua Taratara, and knowing the influence of gadget use on families in St. Anthony Padua Taratara. The research method used is a quantitative approach. The research sample consisted of 619 families taken randomly from 823 families in St. Mary's Parish. Anthony Padua Taratara. The research instrument used was a questionnaire with alternative answers: Strongly Agree (4), Agree (3), Disagree (2), and Disagree (1). The research results obtained show that there is an influence of gadget use on the family. This is proven by the results obtained by Fcount of 65,054 with a significance level of 0.000 <0.005, and a correlation value of 0.308 and a coefficient of determination of 9.5%. So it can be concluded that there is a very low and significant influence on the use of gadgets on the family.